2015
DOI: 10.1080/19485565.2015.1045580
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Environmental Exposures and Height, Hypertension, and Cardiovascular Risk Factors Among Older Adults in India

Abstract: Environmental exposures like rainfall and temperature influence infectious disease exposure and nutrition, two key early life conditions linked to later life health. However, few tests of whether early life environmental exposures impact adult health have been performed, particularly in developing countries. This study examines the effects of experiencing rainfall and temperature shocks during gestation and up through the first four years after birth on measured height, hypertension, and other cardiovascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 83 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…Lastly, it is important to note that in utero exposure to heat has been linked with a range of childhood and adult conditions, and even long term economic prospects. 8 9 10 98 99 Each of these topics warrants closer study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it is important to note that in utero exposure to heat has been linked with a range of childhood and adult conditions, and even long term economic prospects. 8 9 10 98 99 Each of these topics warrants closer study.…”
Section: Discussionmentioning
confidence: 99%
“…This complexity is heightened by the lag times between heat exposure in pregnancy and adverse outcomes, which can be several months with congenital anomalies, for example, as these anomalies might become apparent only at birth. Additionally, lag times can even be decades, with outcomes that manifest in adulthood 8910. Much of the research on climate change and health in low and middle income countries has centred on infectious diseases such as malaria, and in high income countries, the focus has been on heat related mortality among groups such as elderly people or those with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A study using the SAGE and climate research data from India found that exposure to climate shocks in early life was associated with higher risk in adults of developing hypertension later in their life. 27…”
Section: Discussionmentioning
confidence: 99%
“…In India, there are multiple factors could attenuate the seasonality in SCLD. The major factors are temperature and rainfall of the geographical locations, and the periods of searches (year, month and week) [22][23][24][25][26][27]. India has been divided into four major main climatic regions based on temperature and rainfall namely hot & dry, cold, composite and hot & humid [28].…”
Section: Introductionmentioning
confidence: 99%